The Middle Classes and the City - Bacqué, M. author. aut Link
XI, 246 p.
Keywords: What does it mean to be middle class in contemporary global cities? What do the middle classes do to these cities and what do these cities do to the middle classes? Do the middle classes engage in social mix or are they focused on 'people like us'? Based on comparative study this book explores middle-class identities across Paris and London.